e-Resources for effective management of agricultural knowledge - BHARTI, V. K.; BHAN, SURAJ; ., MEETALI; ., DEEPSHIKHA; BHARTI, SANJAY (Journal of Soil and Water Conservation, 2020)
The Information and Communication Technology (ICT) is playing a key role in agricultural growth and development in the country by providing timely and useful information in a demand-driven mode. As a commitment to deliver cost-effective and production-oriented technologies for the welfare of farming community, the ICAR has adopted ICT based information dissemination system. Apart from increasing trends in e-publishing in agricultural sector in the country, it has been noticed that number of print publication has also been increased. The Indian Council of Agricultural Research is leading the country inthe area of agricultural research, education and extension through its wide network of Research Institutes, Krishi Vigyan Kendra and Agricultural Universities (SAUs). In the era of information explosion, Information and Communication Technology is progressively replacing the old methods of information collection, storage and retrieval. The ICAR has initiated projects related to ICT like e-Journals, e-Courses, CeRA, Agroweb, Mobilising Mass Media and interactive multimedia advisory system in order to enhance the overall efficiency of the management and dissemination of agricultural knowledge to different stakeholders of the society. Challenges to the agriculture include increasing the production of agricultural crops as the population continues to grow globally and more so in developing countries. Climate change is also a threat to agriculture besides shrinking land productivity. Now-a-days, Information Communication Technology (ICTs) play an important role in almost all the domains.